IMPLEMENTASI METODE LOCATION BASED SERVICES PADA SISTEM PRESENSI PEGAWAI - Abdullah Ahmad Ma'shum; Dwi Remawati; Bramastyo Wiryawan Yudhanto (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
The attendance system is a digital attendance record, this is needed to evaluate employee attendance data. During the corona virus pandemic, the employee attendance system having some problems related to physical distancing policies, it needs problem solving to solve the problem, it is namely by maximizing the attendance coordinates of each employee, which use Location Based Services (LBS) technology method and haversine formula that functions to calculate the distance of the attendance coordinates with the employee's position. Creating the system using Software Development Life Cycle (SDLC), Waterfall, Node.js, Express.js, Flutter and MySQL as well as a VPS server. The final result of the employee attendance system can run on two platforms, the frontend version on android mobile devices and the backend version on the website. The test results on the employee attendance system received a "reasonable" predicate with an achievement range of 70-74 %. The conclusion of this research is creating the creation of an employee attendance system use location coordinates which is answered the problems on this research.